Application of Cover Type and Rootstock Height to the Success of Mango Grafting - I Kadek Handre Darma Putra; Wawan Pembengo; Suyono Dude; Fitria S Bagu; Fauzan Zakaria; Silvana Apriliani; Mohamad Lihawa; Suparmin Fathan; Ramlan Mustafa (Jurnal Ilmu Pertanian Indonesia, 2025)
The availability of high-quality mango seedlings is a major challenge in improving fruit yield and quality, which can be addressed through vegetative propagation techniques, such as grafting that combines rootstocks with strong root systems and scions from superior varieties. This study aimed to determine the effects of the interaction between cover type and rootstock height on mango grafting success. This study was conducted from July to September 2022. A split-plot design was employed, with the main factor being the cover type (single and mass cover) and the sub-factor being the rootstock height (50 cm and 30 cm). The measured parameters included the time for bud emergence, percentage of bud emergence, number of leaves, and grafting success, with data analyzed using ANOVA and LSD tests at a 5% significance level. The results showed that mass cover significantly influenced grafting success, with an average time of bud emergence of 12.40 days, percentage of bud emergence of 100%, average number of leaf average of 6.90, and grafting success rate of 100%. Conversely, the rootstock height did not significantly affect these parameters. Mass cover has been proven to create an optimal microenvironment for plant growth by maintaining humidity and temperature and protecting plants against extreme environmental conditions. In contrast, grafting incompatibility was detected in certain rootstock height treatments, potentially affecting the nutrient flow and graft quality. In conclusion, mass cover had a dominant effect on grafting success, whereas rootstock height had no significant impact. No interaction was found between cover type and rootstock height in mango grafting. Keywords: cover type, rootstock height, grafting